Teachers’ Implicit Attitudes Toward Ethnic Minority Students: A Systematic Review - Costa, Sara; Langher, Viviana; Pirchio, Sabine (Frontiers in Psychology, 2021)
Although instruments to assess implicit attitudes were introduced more than 20 years ago, there are still few studies in the field of education that use them, despite evidence that teachers with negative implicit attitudes can negatively affect their students' academic performance. This review aims to summarize the results of studies that investigated the relationship between teachers’ implicit ethnic attitudes and students’ achievement. The review was conducted according to PRISMA-statement through searches in the scientific database PsychINFO, PsycARTICLES and ERIC. Nineteen studies were included. Results show that overall teachers (from different school levels and different countries), hold negative implicit attitudes toward ethnic minority students, which play an important role by affecting the academic path of these groups of students. This review highlights the need to continue to use implicit attitudes procedures in future researches, in order to identify those factors that may contribute to the formation and expression of teachers' implicit attitudes; and the need to increase awareness of teachers' implicit attitudes and multicultural practices in teaching programmes.